K-pax - Gordon, Lawrence; Levin, Lloyd; Colesberry, Robert F.; Softley, Iain (Universal City, California Universal, 2002)
A stranger who calls himself Prot seemingly appears out nowhere following a disturbance at New York's Grand Central Station. Claiming to come from the distant planet K-Pax, Prot draws the attention of jaded Dr. Powell whose initial skepticism soon turns to fascination and amazement. Even a team of leading scientists are at a loss to explain Prot's detailed knowledge of the star system he calls home. But with Prot's return to K-Pax fast approaching, the search for answers intensifies and the mystery takes on pulse-quickening proportions.
Screenplay writer, Charles Leavitt ; Executive producer, Susan G. Pollock
Kevin Spacey, Jeff Bridges, Alfre Woodard, Mary McCormack, Peter Gerety, Saul Williams.
Dolby digital.
In English/Francais/Español.
Keywords: Psychic trauma -- Drama; Distress (Psychology) -- Drama; Psychoses -- Drama